AVALIAÇÃO DE BARRAS DE CEREAL ELABORADAS COM CASTANHA DE BARU E DE LICURI - SILVA, Gabrielli Barros; BRITO, Mariana Aparecida; BRITO, Mariana Aparecida; FEGADOLI, Fernanda Pereira; FEGADOLI, Fernanda Pereira; Benedetti, Silvia; Benedetti, Silvia (ANAIS DO ENIC, 2018)
-